OLED Fabrication by Using a Novel Planar Evaporation Technique - Fu-Ching Tung; Yi-Shan Wang; Shih-Hsiang Lai; Chien-Chih Chen; Szu-Hao Chen; Ching-Chiun Wang; Jwo-Huei Jou; Sun-Zen Chen (International Journal of Photoenergy)
Organic light-emitting diode fabrication is suffering from extremely high material wasting during deposition especially using a typical point or even line source. Moreover, the need of depositing a high number of emitters and host(s) with a precise composition control in a single layer makes traditional vapor codeposition systems nearly impossible, unless otherwise with a very low yield. To improve, we have developed a novel thin-film deposition system with a planar source loadable with any premetered solvent-mixed organic compounds, plausibly with no component number limitation. We hence demonstrate experimentally, along with a Monte Carlo simulation, in the report the feasibility of using the technique to deposit on a large area-size substrate various organic materials with a relatively high material utilization rate coupling with high film uniformity. Specifically, nonuniformity of less than ±5% and material utilization rate of greater than 70% have been obtained for the studied films.